How Huawei weathered the storm: Resilience, market conditions or failed sanctions? - Hosuk Lee-Makiyama; Robin Baker (European Centre for International Political Economy (ECIPE), 2024)
Huawei is exhibiting stoic resilience in the face of US sanctions, economic downturns, and the slow pace of 5G investments. There is a narrative that the company has been propped up by the Chinese government, but the key to Huawei's resilience is multifaceted. Through pre-emptive stockpiling and ingenuity, the company has continued to fulfil its base station orders and defend its market shares abroad. Concurrently, Huawei has made an autonomous business decision to reinvest its earnings and intensify R&D to secure its supply chains against political risks and diversify into new business areas. Successful forays into semiconductors, cloud services and energy grids have also been facilitated by a capital structure that lends itself to long-term planning. Huawei's survival is not necessarily a lesson in the futility of sanctions to stifle technological progress. However, it does show that muddled political objectives and inconsistent implementation will yield potentially contrary outcomes. At the same time, factors that contribute to Huawei's resilience also highlight the infighting and vulnerabilities of listed firms like Mavenir, Ericsson and Nokia.
Keywords: 330; Telecommunications equipment suppliers; Corporate success; Corporate growth; China; Telekommunikationsausrüster; Unternehmenserfolg; Unternehmenswachstum; China